Comparison of Seed Tolerance to Low Temperature Between Praxelis Clematidea and Bidens Pilosa and Their Invasion Potential - Zhong, Jundi; Chen, Xiongying; Huang, Siyan; Huang, Yanshi (International Journal of Natural Resources and Environmental Studies, 2026)
To investigate the response mechanisms of seeds of the invasive plants Praxelis clematidea and Bidens pilosa to low-temperature environments and their dispersal potential, this study used the paper culture method in petri dishes. Seeds were subjected to 25°C （room temperature）, 4 °C, 0 °C, and -20 °C for 3 and 6 months. After treatment, germination tests were conducted under suitable conditions, with freshly collected seeds serving as the control (CK). Seed germination and seedling growth indicators were measured to analyze the effects of temperature and treatment duration on seeds and seedlings of the two species. The results showed that germination and seedling growth indicators of both species decreased with longer treatment duration and increased with lower treatment temperatures, but all remained lower than those of the CK. After 6 months at room temperature, all indicators for both species dropped to zero. After 6 months at -20 °C, the germination rates of P. clematidea and B. pilosa decreased by 33.8% and 1.2%, respectively, compared with the CK, with the latter showing a significantly smaller reduction. After 6 months of low-temperature treatment, seedling height, root length, fresh weight, and root-to-shoot ratio of both species were lower than those after 3 months, though most differences were not significant. In conclusion, seeds of P. clematidea and B. pilosa have a certain tolerance to low-temperature environments and can still germinate and establish in new habitats under suitable conditions after low-temperature treatment. Among them, B. pilosa seeds exhibit stronger low-temperature tolerance and have a higher potential risk of northward dispersal.